Synergy changes due to performance level during shot-put: a longitudinal study in the same athlete - Matsunaga, N. (International Journal of Sport & Health Science, 2022)
Synergy refers to the coordination of several muscles and has been shown to be varied in different levels of sports performance. However, how synergy changes with improved sports performance is currently unclear. Thus, the aim of this study was to investigate and track the relationship between synergy and shot-put performance in a single athlete. One shot-put thrower participated in this study. Measurements were taken three times in the span of 15 months just prior to, or after competition. The activity of 16 muscles was recorded and analyzed using non-negative matrix factorization. The participant's personal record in competition improved throughout this study, along with an increase in the number of synergies, comprising of two synergies in the first measurement, and four synergies in the second and third measurements. Additionally, the synergies in the second and third measurements were shown to be unique. Although these data involved only one participant, both the alteration in the number of synergies and the changes to the synergy itself were shown to influence shot-put performance. These results suggest that tracking synergy may be a useful indicator to evaluate the shot-put performance growth process.